Analysis of Mathematical Communication Skills to Students Based on Problem-Solving Construction - Nasrullah Nasrullah (Jurnal Gantang, 2022)
This research aims to systematically analyze students' mathematical communication skills based on the given problem-solving construction from the given math problems. The students involved in this study are class IX SMPN 1 Mangarabombang. The type of research applied is qualitative research with a descriptive approach. The research instruments are Mathematical Ability Test, Mathematical Communication Skills Guidelines, and Interview Guidelines. In this study, triangulation techniques were used to check the validity of the data that had been obtained. Data analysis techniques in this study use model with the following stages: 1. Data Reduction, 2. Data Presentation, and 3. Making Conclusion. The results show that mathematical communication skills can be demonstrated by mathematical modeling, representation of ideas, development of the ability to use mathematical object devices, and connecting algebraic expression to mathematical ideas. To realize this, the researcher understood and mastered mathematical concepts to support solving the given problems. Understanding, in this case, is characterized by indicators not only knowing mathematical concepts but knowing at the time when they are used and how to apply them. Then mastery is to place the mathematical concept in the context of the problem.